Occurrence of Fatal and Nonfatal Adverse Outcomes after Heart Transplantation in Patients with Pretransplant Noncytotoxic HLA Antibodies - Luciano Potena; Andrea Bontadini; Sandra Iannelli; Fiorenza Fruet; Ornella Leone; Francesco Barberini; Laura Borgese; Valentina Manfredini; Marco Masetti; Gaia Magnani; Francesco Fallani; Francesco Grigioni; et al. (Journal of Transplantation)
HLA antibodies (HLA ab) in transplant candidates have been associated with poor outcome. However, clinical relevance of noncytotoxic antibodies after heart transplant (HT) is controversial. By using a Luminex-based HLA screening, we retested pretransplant sera from HT recipients testing negative for cytotoxic HLA ab and for prospective crossmatch. Out of the 173 consecutive patients assayed (52±13y; 16% females; 47% ischemic etiology), 32 (18%) showed pretransplant HLA ab, and 12 (7%) tested positive against both class I and class II HLA. Recipients with any HLA ab had poorer survival than those without (65±9 versus 82±3%; P=0.02), accounting for a doubled independent mortality risk (P=0.04). In addition, HLA-ab detection was associated with increased prevalence of early graft failure (35 versus 15%; P=0.05) and late cellular rejection (29 versus 11%; P=0.03). Of the subgroup of 37 patients suspected for antibody mediated rejection (AMR), the 9 with pretransplant HLA ab were more likely to display pathological AMR grade 2 (P=0.04). By an inexpensive, luminex-based, HLA-screening assay, we were able to detect non-cytotoxic HLA ab predicting fatal and nonfatal adverse outcomes after heart transplant. Allocation strategies and desensitization protocols need to be developed and prospectively tested in these patients.